Multilevel analyses of SCN5A mutations in arrhythmogenic right ventricular dysplasia/cardiomyopathy suggest non-canonical mechanisms for disease pathogenesis. Issue 1 (9th January 2017) - te Riele, Anneline S.J.M.; Agullo-Pascual, Esperanza; James, Cynthia A.; Leo-Macias, Alejandra; Cerrone, Marina; Zhang, Mingliang; Lin, Xianming; Lin, Bin; Rothenberg, Eli; Sobreira, Nara L.; Amat-Alarcon, Nuria; Marsman, Roos F.; et al.
Abstract : Aims: Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy (ARVD/C) is often associated with desmosomal mutations. Recent studies suggest an interaction between the desmosome and sodium channel protein Nav 1.5. We aimed to determine the prevalence and biophysical properties of mutations in SCN5A (the gene encoding Nav 1.5) in ARVD/C. Methods and results: We performed whole-exome sequencing in six ARVD/C patients (33% male, 38.2 ± 12.1 years) without a desmosomal mutation. We found a rare missense variant (p.Arg1898His; R1898H) in SCN5A in one patient. We generated induced pluripotent stem cell-derived cardiomyocytes (hIPSC-CMs) from the patient's peripheral blood mononuclear cells. The variant was then corrected (R1898R) using Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 technology, allowing us to study the impact of the R1898H substitution in the same cellular background. Whole-cell patch clamping revealed a 36% reduction in peak sodium current ( P = 0.002); super-resolution fluorescence microscopy showed reduced abundance of NaV 1.5 ( P = 0.005) and N-Cadherin ( P = 0.026) clusters at the intercalated disc. Subsequently, we sequenced SCN5A in an additional 281 ARVD/C patients (60% male, 34.8 ± 13.7 years, 52% desmosomal mutation-carriers). Five (1.8%) subjects harboured a putatively pathogenic SCN5A variant (p.Tyr416Cys, p.Leu729del, p.Arg1623Ter, p.Ser1787Asn, and p.Val2016Met). SCN5A variants were associated with prolonged QRS duration (119 ± 15 vs. 94 ± 14 ms, P < 0.01) and all SCN5A variant carriers had major structural abnormalities on cardiac imaging. Conclusions: Almost 2% of ARVD/C patients harbour rare SCN5A variants. For one of these variants, we demonstrated reduced sodium current, Nav 1.5 and N-Cadherin clusters at junctional sites. This suggests that Nav 1.5 is in a functional complex with adhesion molecules, and reveals potential non-canonical mechanisms by which Nav 1.5 dysfunction causes cardiomyopathy.